Hometown victory : a coach's story of football, fate, and coming home - Lowe, Keanon; Spizman, Justin (Flatiron Books, 2022)
"The Blindside meets Friday Night Lights in Keanon Lowe's Hometown Victory when an NFL coach returns home after losing a friend to opiods to coach a team of struggling high school kids on a 23-game losing streak. Keanon Lowe was working as an offensive analyst for the San Francisco 49ers when his childhood friend and former high school teammate suddenly died from an opioid overdose. Keanon dropped everything--including the plum NFL job he had been working towards since childhood--leading him to a position as football coach at a struggling high school back in his hometown. At the time, Parkrose High School was in the middle of a 23-game losing streak -- they were the ultimate underdogs. In many ways, the road to Parkrose was paved by Keanon's life-defining experiences -- from a childhood spent dodging racist bullies and finding the support and mentorship he craved on the football team, to an NFL season where he worked closely with Colin Kaepernick as he evolved his sideline protest. Keanon was drawn to the young men on the Parkrose team, and to the school itself. After two years, he pushed them to become conference champions, mentoring countless players along the way. But still, there was that nagging sense that his calling wasn't meant to stop there. He was at that school for a reason. In May 2019, he got his answer when a 19-year-old student entered a Parkrose classroom with a trench coat and shotgun. Keanon disarmed him and pulled the boy into a hug, telling him he cared. In the boy, Keanon saw himself, and the young men he grew up with or mentored along the way -- and weren't so many of them just looking for acceptance, for comfort, for love? With the heart of favorite football classics - The Blindside, Friday Night Lights, Remember the Titans - Keanon's journey at Parkrose is the true account of a life spent striving forward, even when faced with the unimaginable. Hometown Victory is a story about gratitude, service, and most of all, hope"--